Association Between Prior Aspirin Use and Acute Respiratory Distress Syndrome Incidence in At-Risk Patients: A Systematic Review and Meta-Analysis - Liang, Huoyan; Ding, Xianfei; Li, Hongyi; Li, Lifeng; Sun, Tongwen (Frontiers in Pharmacology, 2020)
Background: Recent studies have shown that prior antiplatelet drug use could ameliorate the risk and mortality ofacute respiratory distress syndrome (ARDS). However, the connection between prior acetylsalicylic acid (aspirin) use and the risk of ARDS is unknown. Our primary objective was to perform a meta-analysis on the currently available studies to assess the association between aspirin use prior to ARDS onset and ARDS incidence in at-risk patients. Methods: Two investigators separately searched four research databases: MEDLINE, Embase, Cochrane Library, and Web of Science for relevant articles from the earliest available data through to July 14, 2019. In this paper, we performed a meta-analysis of the fixed effects model using the inverse variance-weighted average method to calculate the pooled odds ratios (ORs) and 95%confidence intervals (CIs). The primary outcome was risk of ARDS, and the secondary outcome was hospital mortality of at-risk patients. Results: This article included seven studies altogether, enrolling 6,764 at-risk patients. Our meta-analysis revealed that, compared to non-aspirin use, prior aspirin use was linked with a significantly lower incidence of ARDS in at-risk patients (OR, 0.78; 95% CI, 0.64–0.96; P = 0.018) with low statistical heterogeneity (I = 1.7%). Additionally, difference between prior aspirin use and non-aspirin use was not remarkable for hospital mortality in at-risk patients (OR, 0.88; 95% CI, 0.73–1.07; P = 0.204), and this analysis did not involve statistical heterogeneity (I = 0%). Conclusions: This article indicates an association between prior aspirin use and a lower incidence of ARDS in at-risk patients, suggesting that aspirin use could potentially lower the risk of ARDS, and the investigation of such an effect is an interesting area for future clinical studies.